Theological Reflections: A Comparative Study of Tafsir al-Tabari and Ginzberg’s The Legends of The Jews on Prophet Ibrahim (PBUH)’S Fiery Furnace Miracle Narratives - AlJahsh, Muhammad Ahmad Ibrahim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This study investigates the narratives of Prophet Ibrahim’s Fiery Furnace Miracle in Islamic and Jewish traditions, focusing on Tafsir al-Tabari and Ginzberg’s The Legends of the Jews. Through a comparative and analytical approach, the research aims to identify similarities and differences in the theological precepts and ethical lessons presented in these sources as well as explore the potential influence of Islamic sources on Ginzberg’s work. The findings reveal that the Qur’anic narrative, as elucidated in Tafsir al-Tabari, maintains its superiority by presenting a concise and focused account of the events, emphasizing the core message of faith, trust in God, and submission to His will. The study also investigates the interconnectedness of religious traditions, highlighting the significance of historical and cultural contexts in shaping religious narratives. The results highlight the potential of comparative studies to foster a greater understanding and appreciation of narratives shared between faiths, and they emphasize the importance of recognizing the interconnectedness of religious traditions in promoting interfaith dialogue and cooperation.